Pengembangan Aplikasi Virtual Reality Objek Sejarah di Kuantan Singingi Sebagai Media Belajar Sejarah Lokal Kelas X SMKN 1 Benai - Saputra, Alkis; ahmal, ahmal; asril, asril (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2023)
This research aims to develop learning media that will be used when learning history at school. This research is a development research using the ADDIE method. The product being developed is an application-based application or can also be accessed through a website, namely a Virtual Reality application that contains historical objects in the Singingi Kuantan. The subject of the trial was to see how students' knowledge developed after using the application, but before being used in learning the application was validated first by a validator consisting of a media validator and material validator which was measured using a Likert scale. In addition, the students who assessed the application consisted of a small group of 12 people and a large group, namely class X TKJ 1 with a total of 32 students. Data was collected descriptively, quantitatively and qualitatively. The results of the study showed that in the trials carried out, the scores were obtained with very good predicates and were suitable for use as learning media in schools in history lessons, more specifically in historical research material.